Probiotic Supplementation Improves Cognitive Function and Mood with Changes in Gut Microbiota in Community-Dwelling Older Adults: A Randomized, Double-Blind, Placebo-Controlled, Multicenter Trial. (17th April 2020) - Kim, Chong-Su; Cha, Lina; Sim, Minju; Jung, Sungwoong; Chun, Woo Young; Baik, Hyun Wook; Shin, Dong-Mi
Abstract: Probiotics have been proposed to ameliorate cognitive impairment and depressive disorder via the gut–brain axis in patients and experimental animal models. However, the beneficial role of probiotics in brain functions of healthy older adults remains unclear. Therefore, a randomized, double-blind, and placebo-controlled multicenter trial was conducted to determine the effects of probiotics on cognition and mood in community-dwelling older adults. Sixty-three healthy elders (≥65 years) consumed either placebo or probiotics containing Bifidobacterium bifidum BGN4 and Bifidobacterium longum BORI for 12 weeks. The gut microbiota was analyzed using 16S rRNA sequencing and bioinformatics. Brain functions were measured using the Consortium to Establish a Registry for Alzheimer's disease, Satisfaction with life scale, stress questionnaire, Geriatric depression scale, and Positive affect and negative affect schedule. Blood brain-derived neurotrophic factor (BDNF) was determined using enzyme-linked immunosorbent assay. Relative abundance of inflammation-causing gut bacteria was significantly reduced at Week 12 in the probiotics group ( p < .05). The probiotics group showed greater improvement in mental flexibility test and stress score than the placebo group ( p < .05). Contrary to placebo, probiotics significantly increased serum BDNF level ( p < .05). Notably, the gut microbes significantly shifted by probiotics ( Eubacterium and Clostridiales) showed significant negative correlation with serum BDNF level only in the probiotics group (RS = −0.37, RS = −0.39, p < .05). In conclusion, probiotics promote mental flexibility and alleviate stress in healthy older adults, along with causing changes in gut microbiota. These results provide evidence supporting health-promoting properties of probiotics as a part of healthy diet in the older adults.